PERGESERAN TRADISI NGAYAH DALAM KEHIDUPAN MASYARAKAT DI BANJAR DAUH RURUNG, DESA BELALANG, KECAMATAN KEDIRI, TABANAN - Anggayasti Angga, Ni Made Ayu Mita; Punia, I Nengah; Krisna Aditya, I.G.N Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This research focuses on the shifting of ngayah tradition which caused by changes of era. The type of research used is qualitative with descriptive and exploratory approaches. The theory used in this research is William F. Ogburn's theory of social change which is a reference for analyzing the occurrence of material and immaterial social changes. The purpose of this study is to describe the process of social change in community life and the things that drive change. this is in the tradition of ngayah in Banjar Dauh Rurung, Belalang Village, Kediri District, Tabanan. The results showed that the ngayah tradition experienced a shift in terms of time in its implementation activities and the means of the ceremonies made. Society is more concerned with effectiveness and time efficiency. Keywords: Shift, The Tradition Of Ngayah, Society